Cerebral pyogranulomatous encephalitis caused by Cladophialophora bantiana in a 15-week-old domestic shorthair kitten - Russell, Elise B (JFMS Open Rep, 2016)
CASE SUMMARY: A case of cerebral phaeohyphomycosis caused by Cladophialophora bantiana is described in a 15-week-old domestic shorthair kitten. RELEVANCE AND NOVEL INFORMATION: Cerebral phaeohyphomycosis is a rare condition in cats caused by dematiaceous fungi. This report describes the clinical and histopathological findings in the youngest case documented in a feline, provides a brief review of aetiology, diagnosis, treatment and prognosis of cerebral phaeohyphomycosis and demonstrates the importance of molecular diagnostics in accurate mycotic species identification.